Accounting Treatment of Operations in Public Catering Services - Razvan Vonea (Agora International Journal of Economical Sciences (AIJES), 2018)
The existing article proposes to bring to light the organization and management approach in conducting the accounting in the food service businesses. I first introduced a short abstract presentation of the food service structure types in the Romanian legislation. I also established an intrinsic relationship between the hotel and hospitality industries as components of the touristic phenomenon exponentially developed worldwide in the last decades. I proposed some accounting cases concerning the accounting entries of different operations referring to the food service business.
Keywords: 330